1998
DOI: 10.1029/98jd00921
|View full text |Cite
|
Sign up to set email alerts
|

The nucleation rate constants and freezing mechanism of nitric acid trihydrate aerosol under stratospheric conditions

Abstract: Abstract. The nucleation rates for submicron-diameter nitric acid trihydrate (NAT) aerosol particles were measured under stratospheric conditions using a temperatureprogramed flow tube and Fourier transform infrared extinction spectroscopy to detect the phase change from liquid to solid. The temperature range from 175 to 155 K was 3 1 examined. The measured nucleation rate constants (in units of cm-s-) are between 3.8 +_ 1.8 x 10 •ø and 9.7 +_ 6.3 x 10 TM for the temperature range between 167.2 and 163.5 K. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 35 publications
8
77
1
Order By: Relevance
“…Salcedo et al (2001) noted that the linear relationship should not be extrapolated and applied to S NAD beyond the range of their experimental data. In the same work Salcedo et al (2001) suggest another linear fit for the activation energy of NAT nucleation as function of the NAT saturation ratio in the range 50<S NAT <110 which relies on their own data set and measurements of NAT nucleation in a flow tube cooled to temperatures below 167.2 K (Bertram and Sloan, 1998b). The earlier settling chamber measurements (Disselkamp et al, 1996;Prenni et al, 1998) have been disregarded by Salcedo et al (2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salcedo et al (2001) noted that the linear relationship should not be extrapolated and applied to S NAD beyond the range of their experimental data. In the same work Salcedo et al (2001) suggest another linear fit for the activation energy of NAT nucleation as function of the NAT saturation ratio in the range 50<S NAT <110 which relies on their own data set and measurements of NAT nucleation in a flow tube cooled to temperatures below 167.2 K (Bertram and Sloan, 1998b). The earlier settling chamber measurements (Disselkamp et al, 1996;Prenni et al, 1998) have been disregarded by Salcedo et al (2001).…”
Section: Resultsmentioning
confidence: 99%
“…The direct crystallisation to NAT was in some studies only observed at temperatures below 180 K and saturation ratios of gas-phase nitric acid with respect to NAT larger than 45 (Bertram and Sloan, 1998b;Salcedo et al, 2001). Such low temperatures and high saturation ratios are not reached in synoptic-scale PSCs.…”
Section: O Möhler Et Al: Homogeneous Nucleation Of Nadmentioning
confidence: 99%
“…(b) : 54 wt% HNO 3 (Salcedo et al, 2001); : 54 wt% HNO 3 (Bertram and Sloan, 1998b). The color coding indicates at which temperature the data were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…(a) : 57 wt%, 60 wt%, and 64 wt% HNO 3 (Salcedo et al, 2001); : 64 wt% HNO 3 (Bertram and Sloan, 1998a). (b) : 54 wt% HNO 3 (Salcedo et al, 2001); : 54 wt% HNO 3 (Bertram and Sloan, 1998b). The color coding indicates at which temperature the data were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…There are several basic AFT designs (Bertram & Sloan, 1998;Chelf & Martin, 2001;Cziczo & Abbatt, 1999;Hung, Malinowski, & Martin, 2002;Norman, Miller, & Worsnop, 2002;Prenni, Wise, Brooks, & Tolbert, 2001;Wise, Garland, & Tolbert, 2004), but they differ in only four main respects: tube diameter and length, which determine the flow velocities employed; optical design (transverse or axial infrared beam); the presence or absence of right-angle bends; and orientation with respect to the gravity vector. A characteristic feature of these systems, which differentiates them from other laminar flow tubes-for example, those used to study homogeneous vapour nucleation-is the existence of large temperature steps, which, for the cases reported here, can introduce temperature differences as high as 100 K between the gas/aerosol flow and the tube wall.…”
Section: Introductionmentioning
confidence: 99%